THE EFFECT OF AMOUNT OF NATURAL ZEOLIT CATALYST IN PRODUCT OF POLYPROPILENE (PP) PLASTIC WASTE PYROLYSIS (Jurnal Bahan Alam Terbarukan, 2015)
To overcome the waste problem, especially plastic waste , environmental concerned scientists from various disciplines have conducted various research and actions. Catalytic pyrolysis processes was chosen as an alternative method to recycle plastic waste. The purpose of this experiment was to determine the effect of natural zeolit catalyst on the pyrolysis process with oxygen-free conditions to obtain maximum hydrocarbon compounds (gasoline fraction in C5-C9). The process of pyrolysis was conducted in 3.5 dm3 unstirred stainless steel semi-batch reactor. This process operated at atmospheric pressure with nitrogen injection. Plastic waste that used in this particular paper was 50 grams of polypropylene (PP). In pyrolysis process, natural zeolite catalysts was added 2,5 gram (5% weight of natural zeolite per weight of plastic waste samples), 5 gram (10% ), and 10 gram (20%). Temperature of pyrolysis was 450°C and were maintained until 30 minutes. Steam that produced from pyrolisis was condensed and analysed by gas chromatography–mass spectrometry (GC-MS) to determine yield of hydrocarbons produced. From the analysis of GC-MS, liquid products of pyrolysis contained lots of aromatic hydrocarbons. The optimal amount of catalyst that produce liquid with hydrocarbon compound that has the quality of gasoline was 10 gram (20%) with ≤C9 composition as 29,16% n-paraffin, 9,22% cycloparaffin, and 61,64% aromatics.